Fast Tracking Recovery: Prioritising Agriculture - Technical Centre for Agricultural and Rural Cooperation; Inter-American Institute for Cooperation on Agriculture (Technical Centre for Agricultural and Rural Cooperation, 2010)
There's no disaster that can't become a blessing, and no blessing that can't become a disaster